A new control strategy for PMSG based wind turbine to improve power smoothing - Gholami, Mehrdad; Shahryari, Om-Kolsoom (Kurdistan Journal of Applied Research, 2017)
This paper presents a new simple control strategy for direct driven PMSG wind turbines, using no wind speed sensor. There are several strategies for wind turbine control. Operation of different strategies in terms of power smoothing is compared. New strategy is proposed to have more power smoothing. Performance of the proposed strategy is evaluated by MATLAB/ Simulink simulations and its validity and effectiveness are verified.